(untitled) (Journal of Medicine, 2014)
Pseudoxanthomaelasticum (PXE) is amendelian autosomal recessive disorder characterised pathologically by elastic fibre mineralisation and clinically by angioid streaks, yellow skin papules and cardiovascular involvement. A case of PXE which manifested with cutaneous features along with nephrocalcinosis was diagnosed recently in Medicine department of Dhaka Medical College Hospital which is a rarity of its own. DOI: http://dx.doi.org/10.3329/jom.v15i2.20701 J MEDICINE 2014; 15 : 149-152